2006
DOI: 10.1007/s00417-006-0332-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal triamcinolone acetonide for treatment of acute nonarteritic anterior ischemic optic neuropathy

Abstract: The clinical courses of all three patients presented suggest that an intravitreal high-dosage injection of triamcinolone acetonide may not be markedly effective in increasing visual acuity after acute NAION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 6 publications
0
35
1
2
Order By: Relevance
“…Use of intravitreal triamcinolone acetonide for treatment of NA-AION There have recently been two contradictory studies on this topic [34,35]. Jonas et al [34], in three patients, found that it had no beneficial effect on visual acuity.…”
Section: Discussionmentioning
confidence: 97%
“…Use of intravitreal triamcinolone acetonide for treatment of NA-AION There have recently been two contradictory studies on this topic [34,35]. Jonas et al [34], in three patients, found that it had no beneficial effect on visual acuity.…”
Section: Discussionmentioning
confidence: 97%
“…Studies involving intravitreal steroid injection [10][11][12][13] have demonstrated improvement in visual acuity over 80% of reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, although avoiding systemic toxicity, intravitreal steroids carry a significant risk of ocular complications such as glaucoma and cataract. 14 Bevacizumab is a local therapy that has potent antiinflammatory properties, and has been used extensively to treat edema of the retina in a safe and efficacious manner.…”
Section: Introductionmentioning
confidence: 99%
“…Jonas et al [35], in three patients, found that it had no beneficial effect on visual acuity. Kaderli et al [36], in four eyes, reported visual acuity improvement, but without any improvement in visual fields; however, that study had some notable flaws [37].…”
Section: Management Of Na-aionmentioning
confidence: 93%